The impact of marketing approach changes to schools selection decision - Afriyani Afriyani; Ibnu Harris; Muhammad Adli Fata (BISMA (Bisnis dan Manajemen), 2019)
Maitreyawira Playgroup/Kindergarten School is one of the long standing and reputable educational institutions in Batam. However, promotion strategy needs to be carried out to communicate educational services to the community in order to influence individuals school selection decisions. In this study, there are four variables in the promotional mix element. This research is intended to determine the effectiveness of marketing which is influenced by changes in marketing functions. The data collection method in this study was carried out by distributing questionnaires to the parents whose their children study in the Maitreyawira Playgroup/Kindergarten School in Batam and considered as the new service user who experience the service. The data analysis was conducted into stages such as F test, t test, and multiple linear regression analysis. The results of this study indicate that WOM (word of mouth) has an influence on Maitreyawira Playgroup/Kindergarten school selection decisions, while e-WOM (electronic word-of-mouth) does not influence the decision to choose Maitreyawira Playgroup/Kindergarten schools.Maitreyawira Playgroup/Kindergarten School is one of the long-standing and reputable educational institutions in Batam. However, promotion strategy needs to be carried out to communicate educational services to the community to influence an individuals school selection decisions. In this study, there are four variables in the promotional mix element. This research is intended to determine the effectiveness of marketing which is influenced by changes in marketing functions. The data collection method in this study was carried out by distributing questionnaires to the parents whose children study in the Maitreyawira Playgroup/Kindergarten School in Batam and considered as the new service user who experiences the service. The data analysis was conducted into stages such as F-test, t-test, and multiple linear regression analysis. The results of this study indicate that WoM (word of mouth) influences Maitreyawira Playgroup/Kindergarten school selection decisions, while e-WoM (electronic word-of-mouth) does not influence the decision to choose Maitreyawira Playgroup/Kindergarten schools. KeywordsWoM; e-WoM; schools selection decision